WONOSOBO FOOTBALL TRAINING CENTER WITH A FUTURISTIC ARCHITECTURAL APPROACH - ardani; Hermawan Hermawan; Adinda Septi Hendriani (Nacreva Publisher, 2023)
Football is currently the most popular sport in the world. Among the countries in the world, in Indonesia football is the most popular sport and Surakarta is one of the cities with high fanaticism for the sport of football. In its development, football is now not just a sport to nourish the body, but has become an entertaining sport that can be enjoyed and done by anyone. In addition, football has now led to a competitive match that requires a victory and achievement. Training facilities are used to shape the character of players so that later they can excel and can improve the quality of a professional football club. So the existence of a Wonosobo Football Training Center in Wonosobo is very important. This is closely related to the coaching and training process of a professional football club. The representative and complete facilities of the Wonosobo Football Training Center in Wonosobo are one of the benchmarks and mirrors of the professionalism and progress of a football club. The Wonosobo Football Training Center area planning in Wonosobo uses a futuristic architectural design. By applying the elements of football which are then transformed into appropriate building forms by applying modern buildings and the use of modern materials by emphasizing the design of free, flowing forms and spaces and avoiding planning norms that tend to be rigid and binding. So that it can support the expression of the building and can accommodate all activities related to football, especially proportional football learning.